Preliminary Star Rating System for Four Wheelers Owners in Surat City - Patel, Sushil A; Bansal , Neha R; Jariwala , Vishal; Panchal , Shaishav J (National Journal of Community Medicine, 2010)
This cross-sectional study among 100 owners of four wheelers, using a pre-tested interview schedule, explores pertinent variables on various aspects relating to the fuel consumption patterns of their vehicles with the objective of developing a preliminary star rating systems for the vehicles & the practices adopted by their owners. The aim of the study is to inform consumers on potential fuel consumption of vehicles in order to encourage practices which lead to consumption of less fuel and promote adoption of environment friendly practices and technologies on the long run.